Penerapan Model Visualization, Auditory, Kinesthetic Berbantuan Media Animasi untuk Meningkatkan Minat dan Hasil Belajar IPA Materi Lapisan Bumi - Purwanti, Heni Agus (LP3 Universitas Negeri Semarang, 2020)
The effort to increase the learning interest can be performed by applying the learning methods that consider studentâ€™s characteristic and using the suitable media for the learning object. The Visualization, Auditory, Kinesthetic learning model assisted by animation can be the alternative solution. The research aimed to get the increase of learning interest as well as the learning outcomes as it was applied in the learning process of Earth Structure.Â The subject of the research were students of SMP Negeri 2 Cepiring in the VIIA class of the second semester in 2017/2018 academic year. The research used classroom action research method, consisting of two cycles. Each cycle consisted of planning, acting, observing and reflecting steps. The technique of data collecting was through observation, questionnaire, test and documentation. The data was analyzed by comparative and descriptive methods. The results showed that the learning interest increased for 26.79% then the learning outcome increased for 19.39% on cognitive aspect and 10.71% on skills aspect. It can be concluded that the implementation of Visualization, Auditory, Kinesthetic learning model assisted by animation in Earth Structure learning process can increase the learning interest as well as the learning outcomes of SMP Negeri 2 Cepiring students in the VIIA class of the second semester in 2017/2018 academic year.